Thiamine-Responsive Megaloblastic Anemia Syndrome Combined with Thalassemia Trait: A Rare Association - Mabrouk, Abdelazim; Aburawi, Elhadi H. (Ibnosina Journal of Medicine and Biomedical Sciences, 2023)
Introduction Thiamine-responsive megaloblastic anemia syndrome (TRMA, OMIM reference 249270), also known as Rogers' syndrome, is a rare type of anemia characterized by the triad megaloblastic anemia, sensorineural hearing loss, and diabetes mellitus (DM). Disturbance of thiamine transport into cells results from homozygous or compound heterozygous mutations in the SLC19A2 gene.Case Report We report the case of an 8-year-old girl who presented at age 4 years with anemia. She had a combined hematological profile of microcytic and macrocytic anemia. The parents refused bone marrow aspiration and genetic diagnosis. Hemoglobin electrophoresis established the thalassemia trait. She was later confirmed to have sensorineural deafness and monogenic DM. A tentative TRMA diagnosis was based on megaloblastic anemia, sensorineural deafness, and monogenic DM triad. The patient was treated empirically with a daily dose of thiamine 200 mg; her hemoglobin level normalized, but the deafness and DM did not improve.Conclusion In routine practice, patients with TRMA must be evaluated thoroughly for other causes of megaloblastic anemia, including therapeutic thiamine trials in the presence of sensorineural deafness or DM. These patients should be followed throughout their life span both for DM and to control their response to thiamine therapy for megaloblastic anemia.
Keywords: monogenic diabetes mellitus; sensorineural deafness; megaloblastic anemia; vitamin B1 deficiency; thalassemia trait